Perspectives on the use of small barbarian contingents in the late roman army - Ruchesi, Fernando C. (AADEC - UNL, 2017)
The aim of this article is to analyse the use of small barbarian groups by the Roman Empire, from the end of the fourth century to the beginning of the fifth. Iwill address topics such as the modalities of use of these barbarian contingents in the late Roman army. Secondly, I will enquire on their integration into theimperial structures according to such modalities. Finally, I will also focus on the representations of such contingents by the contemporary authors.